2019
DOI: 10.1126/science.aaw4104
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for eIF2B inhibition in integrated stress response

Abstract: No statistical methods were used to predetermine sample size. The experiments were not randomized. The investigators were not blinded to allocation during experiments and outcome assessment. Purification of human eIF2The α-, β-, and γ-subunits of human eIF2, and the eIF2-specific chaperone protein human Cdc123 (33) were co-expressed in FreeStyle 293-F cells, using the four pEBMulti-Neo plasmid vectors (Wako), and eIF2γ was expressed with C-terminal FLAG and His8 tags. The cells were lysed in buffer A [20 mM ME… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(167 citation statements)
references
References 55 publications
7
157
3
Order By: Relevance
“…Noteworthy, the eIF5-CTD shares a common topology with the CTD of the ε subunit of the nucleotide exchange factor eIF2B (16); they both fold into a W2-type HEAT domain (27) mediating contacts of both factors with the eIF2β-NTT and eIF2γ (31). Based on our structure, the arrangement of the eIF5-CTD HEAT domain binding site on eIF2γ in the context of the 43S PIC is similar to that of the eIF2Bε-CTD HEAT domain in the context of the recently solved eIF2-eIF2B complex (32,33).…”
Section: The Eif5 C-terminal Domain (Ctd) In the Context Of The 43s Picsupporting
confidence: 55%
“…Noteworthy, the eIF5-CTD shares a common topology with the CTD of the ε subunit of the nucleotide exchange factor eIF2B (16); they both fold into a W2-type HEAT domain (27) mediating contacts of both factors with the eIF2β-NTT and eIF2γ (31). Based on our structure, the arrangement of the eIF5-CTD HEAT domain binding site on eIF2γ in the context of the 43S PIC is similar to that of the eIF2Bε-CTD HEAT domain in the context of the recently solved eIF2-eIF2B complex (32,33).…”
Section: The Eif5 C-terminal Domain (Ctd) In the Context Of The 43s Picsupporting
confidence: 55%
“…Finally, there is an unassigned density on top of the β-propeller of eIF3b in contact with eIF2γ, which is more prominently seen in py48S-closed-eIF3 ( Figures 1A, 1D, 2C, 2F, 3A, 3B, 3E and based on its size and proximity to eIF3i or to the C-terminal domain of eIF5 based on the contacts of eIF2γ with the structurally homologous heat domain of eIF2Bε (Kashiwagi et al, 2019;Kenner et al, 2019); although further studies are required to identify it with confidence.…”
Section: Eif3b Bound On the Subunit Interface Of 40smentioning
confidence: 99%
“…Structures of eIF2B bound to eIF2 [17][18][19][20] revealed that multiple eIF2B subunits mediate binding of the eIF2 heterotrimer. In humans, eIF2a binds across the decamer symmetry interface, bridging the eIF2Bb and eIF2Bd subunits [17,18]. Mutational analyses based on these structures demonstrated that the composite binding surface present in the full eIF2B decamer substantially enhances recruitment of eIF2a.…”
Section: Interactions With Eif2 and Phosphorylated Eif2mentioning
confidence: 99%